ANALISA AKUNTANSI PENDAPATAN PADA REGINA FLORIST MEDAN - Vivia Anjelina Sihombing; Minasari Nasution (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
As times progress and people's tastes increase as well as consumers who become smarter and smarter in choosing flower board shops, we have to further improve the quality and service in our flower board shops.The data analysis method used in this research is a quantitative method. The quantitative method is carried out using descriptive analysis, namely by collecting and combining all the data needed in the research for later analysis.So, it can be concluded that from the 7 Accounting Cycles that are in accordance with the SAK - EMKM Procedures, only a few procedures exist, namely Transactions, Daily Journals, and Income Calculations which are carried out on the Regina Florist Flower Board. Based on the results of sales research on Mr. Dedy's Regina Florist Flower Board business in Medan City, Medan City District, it can be concluded that the Regina Florist Flower Board only uses transactions, daily journals and income table calculations and has not implemented income accounting in accordance with SAK EMKM Chapter 14 Paragraph 14.2. which has been stipulated.